PERLINDUNGAN HUKUM DEBITOR TERHADAP EKSEKUSI SEPIHAK OBJEK JAMINAN FIDUSIA (Studi kasus Pasca Putusan Nomor 71/PUU-XIX/2021) - Grezilia Latuihamllo (2022)
Legal protection is an effort to protect someone from an arbitrary act that arises because of a dispute in this case related to an agreement that has the potential to create legal uncertainty and protection for the parties in this case the debtor who feels disadvantaged for legal uncertainty. and the absence of protection for himself and the objects that are the object of the agreed fiduciary guarantee. However, based on the issuance of the Constitutional Court Decision Number 18/PUU-XVII/2019 which prohibits the implementation of unilateral executions on its own power and tends to violate the law, in line with article 18 paragraph (1) letter d which provides guidance for every business actor in carrying out unilateral action relating to goods purchased by consumers in installments. because unilateral actions in this case include the withdrawal or execution of the object of fiduciary security without the consent of the debtor. So if in this case there is no agreement regarding the existence of 'breach of promise' then it must be proven in court through legal remedies. The problems studied in this study are how the name of the execution is carried out in accordance with the applicable laws and regulations and how is the legal protection for debtors in the implementation of unilateral execution of fiduciary guarantee objects. This research is a normative juridical research (Case Study), The results of this study state that the execution of the object of fiduciary security according to article 195 (1) HIR or 206 Rbg is absolutely submitted to the first court institution (District Court) following legal procedures or correct implementation procedures Therefore, the legal protection contained in Article 28D paragraph (1), 28G paragraph (1), 28H paragraph (4) regarding the right to personal protection and property protection for objects under their control may not be taken by experts arbitrarily. The authority and protection that has been guaranteed is also in the Constitutional Court's decision number 18/PUU-XVII/2019 and so that in this case the creditor does not unilaterally withdraw the object of the fiduciary guarantee